RETRACTED: Evaluasi Proses Berpikir Kreatif Berdasarkan Model Wallas Bagi Siswa SMP Dalam Menyelesaikan Masalah Matematika - Mujib, Mujib; Risqi Maharani, Hevy; Sukestiyarno, YL (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
It is difficult for junior high school teachers to position and nurture their students who are still in transition in creative thinking when solving math problems. This study evaluates students' creative thinking process based on Wallas model (2014). The four stages of the creative thinking process according to Wallas include the preparatory, incubation, illumination, and verification phases. The purpose of this study is to describe the creative thinking process of students based on their basic ability level in solving math problems. This research applies giving test of geometric crater thinking ability by looking at homogenous student in kemampuandan interview for deepening. Subjects of junior high school students who categorized on the ability of high, medium, and low after the ability test. Variable of this research is the existence of junior high school students in solving math problems. By using qualitative descriptive method, data is analyzed through classification stage, data representation, and conclusion. In order to complete the results of data groupings used interview techniques to perform data triangulation. The results showed 1) there were 23.33% of students not complete and only reached the preparation stage, called the low category category; 2) there are 60% of students reach the illumination stage even though to this stage students take a long time, called the middle category category; And 3) 16.67% of students have been completed until the verification stage, called the high category category. Based on the deepening of the triangulation of the interviews, the students are correct in that category. For students with low and medium capability categories still require assistance when experiencing barriers to their creative thinking process, while high ability category students need enrichment material